Resposta de genótipos de Eucalyptus à vespa-da-galha Leptocybe invasa Fisher & La Salle, 2004 (Hymenoptera: Eulophidae) - Dantas, José Oliveira (2019)
The gall wasp Leptocybe invasa originates from Australia. It reproduces by parthenogenesis (telitoca) exclusively in eucalyptus with great power of infestation. Gall wasps lay eggs in leaf midribs, petioles and young branches inducing gall formation, causing the growing shoot tips to dry out and outgrowth of axillary buds, preventing normal plant growth and in cases of more severe attack plant death. However, there are resistant eucalyptus genotypes and genotypes susceptible to gall formation. In order to investigate whether the resistance to gall formation has physical or chemical origin, the anatomy and chemical composition of ten genotypes were analyzed. At the same time, the first occurrence of galls in Eucalyptus globulus, was recorded in the northeast of Brazil. For physical or anatomical analysis, tissue sections of leaves, petioles and young branches of eucalyptus genotypes were cut into a microtome, observed and photographed using the image analysis software Image Pro Plus®. The essential oils of eucalyptus genotypes were analyzed by gas chromatography and mass spectrophotometry. Wasp oviposition was observed in resistant genotypes, but without gall formation. In susceptible genotypes, galls were produced by deformations in the structures and a significant decrease in the vascular bundle areas of leaf midrib and petioles. There was difference in the chemical composition of the essential oils between the resistant and susceptible genotypes, and twelve constituents were detected only in the oils of the resistant genotypes. Therefore, resistance has probably not physical origin, since wasp oviposition occurs in resistant genotypes, hence resistance to gall formation must be chemical, induced by the synergism of essential oil constituents.